Signless and normalized Laplacian spectrums of the power graph and its supergraphs of certain finite groups - Hamzeh, Asma (Journal of the Indonesian Mathematical Society, 2018)
‎The aim of this article is to compute the signless and normalized Laplacian spectrums of the power graph‎, ‎its main supergraph and cyclic graph of dihedral and dicyclic groups‎.